Performance-Based Seismic Design of Tall Reinforced Concrete Buildings for Disaster Resilience in High-Risk Urban Zones - Dahal, Bipul; Shah, Dipendra; Pudasaini, Bishal; Gupta, Bishal Kumar; Sedhai, Bibek; Shrestha, Deep (Journal of Multidisciplinary Research Advancements, 2025)
Tall buildings are crucial in the modern urban era, providing a solution to accommodating the rising population density and addressing the land scarcity problem. Despite mitigating population density, constructing tall buildings is complex, as their structural safety under seismic loading remains a significant challenge, particularly in a seismically active region such as Nepal. Performance-Based Design (PBD) is an advanced structural engineering approach that prioritises the design of buildings based on their expected performance under various seismic loading scenarios. This study focuses on the seismic-resistant design of a 16-storey Reinforced Concrete (RC) shear-wall-framed tall building using a Performance-Based Design approach. The structure was modelled and analysed using ETABS software, in accordance with NBC 105:2020. Linear static and response spectrum analyses were performed, followed by a non-linear static pushover analysis for performance evaluation using FEMA 440 equivalent linearization. The results confirmed that all structural components met strength and serviceability criteria. The pushover analysis revealed that plastic hinges formed primarily in beams, indicating a ductile failure mode. The capacity curve and performance point were obtained, indicating that the overall performance level met the Life Safety criteria for the Design Basis Earthquake. The study concludes that the PBD approach effectively ensures seismic resilience and recommends its expanded use for essential structures in high-risk zones.